The design, development and evaluation of TPSACK courseware to facilitate the art and design education students artistic skills knowledge / Roslaili Anuar, Shahriman Zainal Abidin and Wan Zamani Wan Zakaria. - Anuar, Roslaili; Zainal Abidin, Shahriman; Wan Zakaria, Wan Zamani (2018)
This study examines the effectiveness of the TPSACK courseware which was developed with artistic skills practice to discover the Technological, Pedagogical and Content Knowledge components in the design of the courseware. The courseware was developed based on Dick and Carey Instructional Design Model (2009) to address instruction as an entire system and focusing on the inter-relationship between various factors such as context, content, learning and instruction. A total of 130 respondents Art and Design Education (ADE) group were selected to analyse the TPSACK courseware. The courseware is aimed to develop the students’ artistic skills using technological assistance. The artistic skills included in the courseware are vital for students in preparation of becoming a future art educator. The TPSACK courseware was evaluated using questionnaire with a 5-point Likert scale comprising elements of interface design, content, artistic skills practice and the usability of the courseware. The findings revealed that the courseware indicated satisfactory and appropriate practices of artistic skills for Art students to improve their personal skills. Not only that, the study also suggests that the Dick and Carey Instructional model (2009) will be an ideal model to provide an instructional framework for courseware development.